Determination of fracture toughness of propylene polymers at different operating temperatures - Salazar, A. (2014)
The influence of the temperature on the fracture parameters of three types of polypropylenes under static loading conditions has been analyzed. Single-phase polypropylene homopolymer and random ethylene?propylene copolymer were tested slightly above their glass transition temperatures (within the ductile-to-brittle transition region), and well below and above them; heterophasic ethylene?propylene block copolymers were tested on the range of temperatures from above the glass transition temperature of propylene matrix to below the glass transition temperature of the elastomer phase. Attending to the mechanical response, suitable Fracture Mechanics approaches were used. Fracture toughness increased with temperature for single-phase polymers but block copolymers were not temperature sensitive for the range of temperatures above the glass transition temperature of the elastomeric phase despite their variation on the mechanical properties.